Use of access to information law in the process of competitive intelligence in the context of the private health in brasil: An analysis in sulamerica insurance - Jorge, Carlos Francisco Bitencourt [UNESP]; Nascimento, Natália Marinho Do [UNESP]; de Souza, Juliete Susan Ferreira; Santarém, Vinícius [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; Vitoriano, Marcia Cristina de Carvalho Pazin [UNESP] (My University, 2019)
The use of information and knowledge is essential for the competitive intelligence process occurs in enterprise environments. It is considered that with the enactment of Law 12.527 – Information Access Law, new perspectives in regard to the access to information arose having in mind that all public agencies and private institutions that receive government money should necessarily provide information from public interest to society. However, many economic segments unaware of this new possibility of licit get information for the business. From this perspective, it highlights the importance of using available information from public agencies, through the Information Access Law, in decision making process and in activities related to organizational competitive intelligence process. The research is qualitative nature, bibliographical type, whose method “Case Study” refers to SulAmerica Insurance Company, presented at the 7th SCIP Latin America Summit, competitive intelligence event focused on the business sector. As a result, it was evidenced that the implementation of Information Access Law, propitiated the company to use stemming from scanning and monitoring information in the competitive intelligence process, generating important differentials for business.
El uso de la ley de acceso a la información en el procedimiento de inteligencia competitiva en el contexto de la salud privada en brasil: Un análisis de sulamérica seguros
O uso da lei de acesso à informação no processo de inteligência competitiva no contexto da saúde privada no brasil: Uma análise na sulamérica seguros
Keywords: Competitive intelligence; Health information; Information Access Law; Open data; Private health